PEMBELAJARAN MAHARAH KALAM MENGGUNAKAN METODE CHAIN STORY - Matalino Irgaza, Sulthan; Mukmin; Muhammad Alfath Qaaf (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The teaching of Maharah Kalam to tenth-grade students at MA Raudhatul Ulum Sakatiga still faces obstacles in the form of low confidence in speaking, lack of creativity in developing verbal ideas, and minimal opportunities for students to actively practice Arabic communication. This study aims to analyze the effectiveness of the Chain Story method in improving students' speaking skills (Maharah Kalam). The research used a mixed method approach with a sequential explanatory design, involving quantitative measurements through pre-tests and post-tests as well as N-Gain analysis, which was then supported by qualitative data through observation, interviews, and documentation. The results of the quantitative analysis show that the students' N-Gain scores ranged from 0.08 to 0.53 with an average of 0.2956, which is in the low category. This indicates that the improvement in students' speaking skills after participating in Chain Story learning is still relatively low, although it still shows positive development. Qualitative findings reinforce these results by showing an increase in students' courage to speak, increased participation, interaction between students, and creativity in composing chain stories. Thus, the Chain Story method has been proven to contribute to the improvement of Maharah Kalam, although it has not yet produced a high quantitative improvement. This method remains relevant as an alternative strategy for oral activity-based learning that encourages active and collaborative communication in Arabic language classes.